Impact of digital and conventional rehabilitation aftercare on physical and mental health in orthopedic patients in Germany - Schmidt, Detlef; Fritsch, Julian; Feil, Katharina; Weyland, Susanne; Rittmann, Lena-Marie; Jekauc, Darko (Frontiers in Public Health, 2024)
The integration of digital interventions in health rehabilitation offers promising opportunities to improve patient outcomes. However, empirical studies comparing the effectiveness of digital and traditional rehabilitation interventions remain scarce. This study was designed to evaluate the impact of a digital aftercare program, compared to traditional aftercare and a control group, on both psychological and physical health outcomes in individuals undergoing orthopedic rehabilitation. Additionally, the study also aimed to examine the moderating effects of age and gender. The study employed a partially controlled trial design, engaging a cohort of 805 orthopedic patients, divided into: digIRENA (n=323, digital aftercare), IRENA (n=252, traditional aftercare), and a control group (n=230, without organized aftercare). Measurements took place at four different time points: baseline (start of the rehabilitation program), T1 (13 weeks after the start of rehabilitation, marking the midpoint of aftercare), T2 (26 weeks, marking the end of aftercare), and T3 (43 weeks, to assess the sustainability of aftercare effects). The SF-12 Health Survey was the primary data collection instrument for measuring trends in physical and mental health outcomes over these intervals using repeated measures ANOVA. The results show that rehabilitants in the digIRENA group participated for a longer period of time than rehabilitants in the IRENA group, while the two groups did not differ in terms of motivation at T0 and organized physical activity outside of aftercare at T3. A significant improvement in physical health outcomes was observed in all groups across time, with digIRENA participants showing the greatest improvement. For mental health, all groups showed initial improvements, with the digIRENA group showing the most pronounced increase at T2. Overall, there was a decline in the effects achieved four months after the end of aftercare. When age and gender were included as covariates, the time effect for mental health disappeared, showing a significant time * gender interaction due to significantly lower baseline scores of women compared to men. The results of the study show that digital interventions, in particular the digIRENA program, contribute to improving health rehabilitation outcomes. The digIRENA program and similar digital health interventions may offer potential for improving health rehabilitation aftercare.